Espacialidade carcerária e a instituição de masculinidades entre homens jovens egressos em Ponta Grossa, Paraná - Rossi, Rodrigo (2017)
The purpose of the present thesis is to understand the way in which masculinities are instituted in the daily life of prison space. For this, I take as a space cutout the Hildenbrando de Souza prison located in the city of Ponta Grossa, in Paraná, as a prison spatiality experienced by young men living in its poors peripheries. The temporal cut of the research results from experiences of the investigated group in prison during the youth and that correspond to the period of 2005 to 2013. The researh operationalization involved two stages. The first is related to fieldwork, participant observation, and in-deth interviews with ten male prisioners in the prison system. The second lies in the challenge of constructing the object of study through a methodology of qualitative analysis following its own words and tendencies of meaning that they point out. The studied group trajectories are marked by the territorial experience linked to vulnerability and different illicit acts, diferent spatialities and networks of social relations that corroborate the idea of a trajectory of vulnerability to crime and imprisonment. The normativity constituted in the daily life of prison establishes simultaneous processes of adaptation, disciplinarization and reconfiguration of masculine performances, focusing on the body, food, market exchanges, among other forms of interaction. The prison space is understood as paradoxical because it presents tensions and repositions according to the coexistence between a diversity of subjects, trajectories and axes of inequality and oppression that imply in a type of situated intersectionality. Capable of establish internal differentiations and spatialities proper to the conviviality and spatiality of exile, where inmates who do not follow normativity or who demonstrate deviation to it in the course of their trajectories are banned. The practices of detainees, constituents of the paradoxical prison space, develop through tensions amid the prison system and penitentiary agents, as well as, they can turn to their own collective organization and intervention of penitentiary leaderships and inmates affiliated to the PCC. Therefore, the masculinities built in the daily imprisonment are important references to the constitution and conduct of daily life in prison.